Esports as soft power diplomacy: a comparative review of South Korea, China, the United States, and India - Bandopadhyay, Rajat (Frontiers in Communication, 2026)
Esports has rapidly transformed from a niche digital pastime into a global cultural industry with increasing diplomatic relevance. This study examines how esports operates as a tool of soft power, public diplomacy, and nation branding across four key countries—South Korea, China, the United States, and India—each reflecting distinct governance structures, platform ecosystems, and strategic communication logics. Drawing on contemporary research in soft power, sports diplomacy, and media globalization, the study shows that esports now functions as a youth-driven, digitally mediated channel of international influence. Comparative analysis reveals that South Korea integrates esports into the Hallyu cultural wave; China uses a state-led model tied to digital nationalism and platform sovereignty; the United States projects corporate soft power through global publishers and streaming platforms; and India leverages esports within its Digital India modernization framework. The study identifies core challenges, including governance fragmentation, legitimacy disputes, over-commercialization, integrity risks, and social stigma. It also highlights emerging opportunities in AI-enhanced integrity systems, metaverse-based competitions, and multilateral governance initiatives such as the Olympic Esports Series. Ultimately, the study argues that control over global distribution platforms is becoming as important as game development itself, positioning esports as a transformative diplomatic arena for shaping national identity, cultural visibility, and youth-oriented international engagement.